Computer analysis of the influence of preparation conditions on the porous structure development of nitrogen-doped activated carbons - Mirosław Kwiatkowski; Xin Hu (Journal of CO2 Utilization)
The paper presents the results of a comprehensive analysis of the influence of preparation conditions on the porous structure of nitrogen-doped activated carbons, prepared from urea-formaldehyde resin in a direct one-step activation with potassium hydroxide. The analyses were performed on the basis of nitrogen and carbon dioxide adsorption isotherms via complementary multi-method analysis, i.e. the new numerical clustering-based adsorption process analysis, the non-local density functional theory and the quenched solid density functional theory methods. The analyses carried out showed a significant effect of the activator-to-raw material mass ratio and activation process temperature on the formation of the porous structure. In particular, the analysis of nitrogen adsorption isotherms showed that the development of the porous structure increased with increasing activation temperature and mass ratio up to 0.2, and that the material with the largest volume of the first adsorbed layer was activated carbon obtained at a mass ratio of 0.2 and an activation process temperature of 600 ºC. At a mass ratio of 0.3, a noticeable reduction in the volume of the first adsorbed layer was observed, with an increase in the height of the adsorbate molecules clusters formed. In addition, with increasing mass ratios, an increase in surface heterogeneity was observed, but not exceeding the value of the parameter h = 3, which allows one to conclude that there is a significant influence of the properties of the original raw material on the surface properties of these materials in the case of the activated carbons analysed.